Zinc cooperates with p53 to inhibit the activity of mitochondrial aconitase through reactive oxygen species accumulation - Ya‐Nan Xue; Ya‐Nan Liu; Jing Su; Jiu‐Ling Li; Yao Wu; Rui Guo; Bing‐Bing Yu; Xiao‐Yu Yan; Li‐Chao Zhang; Lian‐Kun Sun; Yang Li (Cancer Medicine, 2019)
Abstract Metabolic reprogramming is a central hallmark of cancer. Therefore, targeting metabolism may provide an effective strategy for identifying promising drug targets for cancer treatment. In prostate cancer, cells undergo metabolic transformation from zinc‐accumulating, citrate‐producing cells to citrate‐oxidizing malignant cells with lower zinc levels and higher mitochondrial aconitase (ACO2) activity. ACO2 is a Krebs cycle enzyme that converts citrate to isocitrate and is sensitive to reactive oxygen species (ROS)‐mediated damage. In this study, we found that the expression of ACO2 is positively correlated with the malignancy of prostate cancer. Both zinc and p53 can lead to an increase in ROS. ACO2 can be a target for remodeling metabolism by sensing changes in the ROS levels of prostate cancer. Our results indicate that targeting ACO2 through zinc and p53 can change prostate cancer metabolism, and thus provides a potential new therapeutic strategy for prostate cancer.